Epidemiology of Giant Cell Tumor in Dr. Hasan Sadikin General Hospital Bandung from 2010-2013 - Kirtana Gunasegaran; M.Naseh Sajadi Budi Irawan; Anglita Yantisetiasti (Althea Medical Journal, 2016)
Background: Giant cell tumor (GCT) of bone is a primary bone tumor. It is commonly seen in South East Asia and found in female around 20–45 years old. The GCT mostly occurs in epiphysis around the knee. The patients normally suffer from pain, swelling, limitation of joint movement, and pathologic fracture. This study aimed to determine the epidemiology of GCT of the bone based on age, sex, location, type, metastases, and recurrence in Dr. Hasan Sadikin General Hospital Bandung.Methods: A descriptive study with retrospective cohort using total sampling method was used to obtain 33 medical records of patients with GCT of bone in Department of Orthopedic & Traumatology and Anatomical Pathology Dr. Hasan Sadikin General Hospital Bandung in the period of January 2010–December 2013.Results: The GCT of bone was mostly found in female of 20 to 29 years old and around 32 years old in male. Distal femur will be the most common site while zygoma, mandibular vertebrae, proximal tibia were rare sites. Twenty nine cases were benign lesion and the rest (4 cases) were malignant. The probability of GCT of bone to metastasize to lungs was very low. Four recurrences occurred within a year.Conclusions: The GCT of bone in male mostly occurs in the third and fourth decade of age. It is found around the knee, mostly benign, rarely metastasize to the lungs and recurrence happens within a year. [AMJ.2016;3(2):244–7] DOI: 10.15850/amj.v3n2.477